The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1108/02656711111162541
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of repairable consecutive‐k‐out‐of‐n: G systems with sensor and repairmen

Abstract: Purpose -The purpose of this paper is to study repairable consecutive-k-out-of-n: systems with r repairmen and a sensing device. Design/methodology/approach -The system can either be a circular C(k, n: G) system or a linear C(k, n: G) system. The working time and the repair time of each component in the system and the sensor detection time are exponentially distributed. Every component after repair is perfect. Each component is classified as either a key component, or an ordinary one according to its priority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Using the following normalizing condition 8 ∑ k=0 P k (∞) = 1 (8) we substitute (8) in last row in (7) to yield…”
Section: Model Formulationmentioning
confidence: 99%
“…Using the following normalizing condition 8 ∑ k=0 P k (∞) = 1 (8) we substitute (8) in last row in (7) to yield…”
Section: Model Formulationmentioning
confidence: 99%
“…They evaluated state transition probabilities and important reliability measures using a generalized transition probability definition. Krishnan and Somasundaram (2011) assessed the performance metrics of consecutive-k-out-of-n: G system having sensor and r repair persons. They used the Laplace transform and concluded that a use of sensor improves the system performance.…”
Section: Introductionmentioning
confidence: 99%
“…(1999) studied reliability for ( n , f , k ) system in which the system fails when consecutive k components out of n fail; Liang et al. (2010) studied exact reliability formula for consecutive k -out-of- n repairable systems; Krishnan and Somasundaram (2011) deliberated on reliability analysis of repairable consecutive k -out-of- n : G system sensor and repairman; Goyal et al. (2017) premeditated sensitivity analysis of a three-unit series system under k -out-of- n : G redundancy; Sharma and Kumar (2017) premeditated availability improvement for the successive k -out-of- n machine system using standby with multiple working vacations.…”
Section: Introductionmentioning
confidence: 99%